Calibration of airborne L-, X-, and P-band fully polarimetric SAR systems using various corner reflectors - Algafsh, Abdullah (Department of Electrical Engineering, 2018)
Synthetic aperture radar polarimetry is one of the current developments in the field of remote sensing, due to the ability of delivering more information on the physical properties of the surface. It is known as the science of acquiring, processing and analysing the polarisation state in an electromagnetic field. The increase of information with respect to scalar radar comes at a price, not only for the high cost of building the radar system and processing the data or increasing the complexity of the design, but also for the amount of effort needed to calibrate the data. Synthetic aperture radar polarimetric calibration is an essential pre- processing stage for the correction of distortion interference which is caused by the system inaccuracies as well as atmospheric effects. Our goal, with this thesis, is to use multiple passive point targets to establish the difference between fully, and compact polarimetric synthetic aperture radar systems on both calibration, and the effects of penetration. First, we detail the selection, design, manufacture, and deployment of different passive point targets in the field for acquiring X- and P-band synthetic aperture radar data in the Netherlands. We started by presenting the selection and design of multiple passive point targets. These were a combination of classic trihedral and dihedral corner reflectors, as well as gridded trihedral and dihedral corner reflectors. Additionally, we detailed the construction of these corner reflectors. The number of constructed corner reflector totalled sixteen, where six are for X-band and six for P-band, as well as four gridded corner reflectors for X-band. Finally, we present the deployment of the corner reflectors at three different sites with carefully surveyed and oriented positions. a Then, we present the calibration of three different fully polarimetric synthetic aperture radar sensors. The first sensor is the L-band synthetic aperture radar sensor and we acquired data using two square trihedral corner reflectors. The calibration includes an evaluation of two crosstalk methods, which are the Quegan and the Ainsworth methods. The results showed that the crosstalk parameters for the Quegan method are all between -17 dB to -21 dB before calibration, while there is a small improvement in the range of 3 dB after calibration. While the Ainsworth method shows around -20 dB before calibration, and around -40 dB after calibration. Moreover, the phase, channel imbalance, and radiometric calibration were corrected using the two corner reflectors. Furthermore, the other two synthetic aperture radar sensors are X- and P-band synthetic aperture radar sensors, and we acquired polarimetric data using our sixteen corner reflectors. The calibration includes the crosstalk estimation, and correction using the Ainsworth method and the results showed the crosstalk parameters before calibration for X-band are around -23 dB, and they are around -43 dB after calibration, while crosstalk parameters before calibration for P-band are around -10 dB, and they are around -30 dB after calibration. The calibration also includes the phase, channel imbalance, and radiometric calibration, as well as geometric correction and signal noise ration measurement, for both X- and P-band. Next, we present the performance of gridded trihedral and dihedral corner reflectors using an X-band synthetic aperture radar system. The results showed both gridded trihedral and dihedral reflectors are perfect targets for correcting the amplitude compared to classical corner reflectors; however, it is not possible to use the gridded reflectors to correct the phase as we need a return from two channels to have a zero-phase difference between the polarisation channels H - V. Furthermore, we detail the compact polarimetric calibration over three com- pact polarimetric modes using a square trihedral corner reflector for the X-band dataset. The results showed no change in the π/mode while a 90ᵒ phase bias showed in the CTLR mode. Finally, the DCP mode showed a 64.43° phase difference, and it was corrected to have a zero phase, and the channel imbalance was very high at 45.92, the channels were adjusted to have a channel imbalance of 1. b Finally, an experiment to measure the penetration and reduction of P-band signal from a synthetic aperture radar system was performed using two triangular trihedral corner reflectors. Both of them have 1.5 m inner leg dimensions. The first triangular trihedral corner reflector was deployed in a deciduous grove of trees, while the other one was deployed a 10 m distance away on a grass covered field. After system calibration based on the reflector in the clear, the results showed a reduction of 0.6 dB in the HH channel, with 2.28 dB in the W channel. The larger attenuation at W is attributable to the vertical structure of the trees. Additionally, we measured the polarimetric degradation of the triangular trihedral corner reflector immersed in vegetation (trees). Further, after calibration, the co-polarisation phase difference is zero degrees for the triangular corner reflector which was outside the trees, and 62.85ᵒ for the corner reflector inside the trees. The designed and fabricated X- and P-band SAR can work operationally with the calibration parameters obtained in this thesis. The data generated through the calibration experiments can be exploited for further applications.